Influence of L-dopa on subtle motor signs in heterozygous Parkin- and PINK1 mutation carriers. (September 2017) - Weissbach, Anne; König, Inke R.; Hückelheim, Katja; Pramstaller, Peter P.; Werner, Elisa; Brüggemann, Norbert; Tadic, Vera; Lohmann, Katja; Bäumer, Tobias; Münchau, Alexander; Kasten, Meike; Klein, Christine
Abstract: Introduction: A latent nigrostriatal deficit and its possible clinical consequences in asymptomatic heterozygous Parkin and PINK1 mutation carriers (AMC) have been a matter of investigation in recent years. Notably, mild Parkinsonian signs in heterozygous mutation carriers can be so subtle that they may be missed if not specifically investigated. Methods: We studied 15 heterozygous Parkin and PINK1 AMC and 18 age- and sex-matched mutation-negative controls using a standardized video, instructing the probands to perform relevant parts of the UPDRS III to investigate fine motor movements at baseline and after first-time L-Dopa administration. Additionally, available UPDRS III scores of mutation carriers from the past ten years were reviewed. Results: AMC showed a reduced number of fine motor movements per second compared to controls at baseline ( p = 0.04). L-Dopa improved motor performance numerically but non-significantly in AMC (p = 0.2301), but significantly in healthy controls (p = 6.1·10–5). Although none of the AMC reported symptoms, nine showed rigidity, bradykinesia, tremor, and postural instability when the UPDRS III was applied. Mean UPDRSIII scores significantly decreased after L-Dopa administration (p = 0.005), but did not increase over the past ten years. Conclusions: (i) Heterozygous AMC show subtle motor abnormalities when a detailed, specialized motor examination is applied and compared to mutation-negative matched control subjects. (ii) The mild motor deficit present in a subgroup of heterozygous Parkin and PINK1 AMC appears to be non-progressive and responsive to L-dopa administration. (iii) Evaluating motor changes, their progression, and treatment response in AMC can provide valuable insights into possible early disease stages and compensatory mechanisms. Highlights: Parkin/PINK1 AMC show subtle motor abnormalities in specialized motor examination. This motor deficit appears to be non-progressive and responsive to L-dopa administration. Motor changes of AMC provide insights into early disease stages and compensatory mechanisms.